Relationship between duodenal microbiota composition, clinical features at diagnosis, and persistent symptoms in adult Coeliac disease. Issue 8 (August 2021) - Schiepatti, Annalisa; Bacchi, Sara; Biagi, Federico; Panelli, Simona; Betti, Elena; Corazza, Gino Roberto; Capelli, Enrica; Ciccocioppo, Rachele
Abstract: Background: Duodenal dysbiosis has been suggested to possibly influence the clinical manifestations of coeliac disease (CD), both at onset and when symptoms persist despite a gluten-free diet (GFD). AIMS: To evaluate the relationship between duodenal microbiota composition and: i) clinical phenotype of untreated CD (UCD); ii) presence and type of persistent symptoms despite a satisfactory serological and histological response to a strict GFD. Methods: Duodenal microbiota was analyzed by 16S rRNA sequencing and compared with i) clinical features in 12 adult UCD patients; ii) presence/absence and type of persistent symptoms (diarrhea-predominant vs. non-diarrhea predominant) in 25 adult treated coeliac patients (TCD) on a strict GFD. Results: UCD with iron deficiency anemia (IDA) had a pro-inflammatory shift in their duodenal microbiota (reduction of Firmicutes, p = 0.03; increase of beta-Proteobacteria, p = 0.02) than those without IDA. TCD with persistent diarrhea showed a reduction of Actinobacteria ( p = 0.03) and Rothia spp ( p = 0.046) compared to TCD suffering from other type of persistent symptoms. Conclusion: A distinctive duodenal microbiota profile is associated with IDA in UCD, and diarrhea-predominant persistent symptoms in TCD. Clinical interventions may include reconsidering patients presenting with IDA as a specific disease subtype, and dietary rebalancing if diarrhea persists despite histological response to a GFD.